Effect of clopidogrel with aspirin on functional outcome in TIA or minor stroke: CHANCE substudy - Wang, Xianwei (Neurology, 2015)
OBJECTIVE: We compared the effect of clopidogrel plus aspirin vs aspirin alone on functional outcome and quality of life in the Clopidogrel in High-risk Patients with Acute Non-disabling Cerebrovascular Events (CHANCE) trial of aspirin-clopidogrel vs aspirin alone after acute minor stroke or TIA. METHODS: Participants were assessed at 90 days for functional outcome using the modified Rankin Scale (mRS) and quality of life using the EuroQol-5 Dimension (EQ-5D). Poor functional outcome was defined as mRS score of 2–6 at 90 days and poor quality of life as EQ-5D index score of 0.5 or less. RESULTS: Poor functional outcome occurred in 254 patients (9.9%) in the clopidogrel-aspirin group, as compared with 299 (11.6%) in the aspirin group (p = 0.046). Poor quality of life occurred in 142 (5.5%) in the clopidogrel-aspirin group and in 175 (6.8%) in the aspirin group (p = 0.06). Disabling stroke at 90 days occurred in 166 (6.5%) in the clopidogrel-aspirin group and in 219 (8.5%) in the aspirin group (p = 0.01). In stratified analysis by subsequent stroke, there was no difference in 90-day functional outcome and quality of life between the 2 groups. CONCLUSIONS: In patients with minor stroke or TIA, the combination of clopidogrel and aspirin appears to be superior to aspirin alone in improving the 90-day functional outcome, and this is consistent with a reduction in the rate of disabling stroke in the dual antiplatelet arm. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that for patients with acute minor stroke or TIA, clopidogrel plus aspirin compared to aspirin alone improves 90-day functional outcome (absolute reduction of poor outcome 1.70%, 95% confidence interval 0.03%–3.42%).